THE ROLE AND PROSPECTS OF AESTHETIC CRITERIA IN THE PROCESSES OF SOCIO-ECONOMIC DEVELOPMENT - Abdurakhimov Bekhzodjon Bahromjon oglu (World Scientific Research Journal, 2025)
Abstract. In the article, ensuring the interaction of the economy with different spheres of social life, socio-economic problems, new economic views are involved in the continuous struggle against such diseases as infatuation, laziness, etc., which take place in the minds of our people.